Efeito da N-acetilcisteína no sistema da glutationa em rim de camundongos sob administração crônica de aspartame - Brener, Carlos Eduardo de Souza (2017)
Currently, many diabetic, obese, and/or those seeking a healthier lifestyle are looking for foods with a sweet taste, but without the addition of energy, preferring to use sweeteners such as aspartame (ASP). The ASP is widely distributed in products available in the market, especially in those that lack sucrose, and its consumption has been approved for more than 20 years by the FDA (Food and Drug Administration). However, there are concerns and evidences that suggest possible adverse effects of ASP metabolites, resulting in alterations in the antioxidant defense system, especially due to the depletion of glutathione levels (GSH) and the activity of the enzymes dependent on it, causing oxidative damages. Considering that obese and/or diabetic individuals replace the use of sucrose by artificial sweeteners, such as ASP, which produces metabolites capable of causing possible adverse effects, it is of fundamental interest to use antioxidant compounds that reduce the harmful effects caused by the sweetener, which are capable of protecting cellular constituents. Thus, N-acetylcysteine (NAC), an excellent antioxidant, has been shown to be effective in restoring the levels of GSH and enzymes related to its metabolism. Thus, the objective of this work was to evaluate the effect of N-acetylcysteine on biochemical and oxidative parameters in renal tissue of mice receiving chronic oral administration of aspartame. For this, mice (n = 30) were divided into three groups: Control, treated with ASP (80 mg.kg-1, vol) and treated with ASP and NAC (163 mg.kg-1, intraperitoneally), during 90 days. From the 60th day of treatment, the animals of the ASP-NAC group started receiving the dose of 163 mg.kg-1. After the experimental period, the animals were euthanized and their kidneys removed for further analysis. Levene’s test was used to verify whether the data were parametric. Two-way analysis of variance followed by Tukey’s test was performed to assess the differences among the groups. The data of this work showed absence of significant difference between groups studied in the content of substances that react to thiobarbituric acid and carbonyl proteins, indicating that there was no damage in the lipids and proteins in the treatment with ASP in mice. Myeloperoxidase activity (MPO) was similar in the ASP group and in the animals treated with ASP-NAC when compared to the control group. The present study showed that oral administration of ASP (80 mg.kg-1) leads to a significant decrease in CAT activity in renal tissue. There is also a decrease in the content of non-protein thiols in animals treated with ASP. The activity of glutathione-related enzymes such as glutathione peroxidase (GPx), glutathione S-transferase (GST) and glutathione reductase (GR) showed a decrease in the ASP group, as does the enzyme thioredoxin reductase (TrxR). The NAC treatment reversed the activity of the CAT, GPx, GST, GR and TrxR enzymes, showing that this drug is a potential in the treatment of disorders caused by oxidative stress.